2019
DOI: 10.1177/0265407519836170
|View full text |Cite
|
Sign up to set email alerts
|

Less in-person social interaction with peers among U.S. adolescents in the 21st century and links to loneliness

Abstract: In nationally representative samples of U.S. adolescents (age: 13–18) and entering college students, 1976–2017 ( N = 8.2 million), iGen adolescents in the 2010s (vs. previous generations) spent less time on in-person (face-to-face) social interaction with peers, including getting together or socializing with friends, going to parties, going out, dating, going to movies, and riding in cars for fun. College-bound high school seniors in 2016 (vs. the late 1980s) spent an hour less a day engaging in in-person soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
218
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 333 publications
(240 citation statements)
references
References 67 publications
(71 reference statements)
12
218
0
10
Order By: Relevance
“…In the same way, students who present greater general isolation are those who belong to seriously dysfunctional families. Research conducted by other authors collaborate these results [72], whilst others such as Twenge, Spitzburg, and Campbell [73] did not manage to demonstrate that isolation in adolescents is more linked to one type of family over another type. These authors instead found high levels of isolation within adolescents coming from functional families.…”
Section: Discussionmentioning
confidence: 95%
“…In the same way, students who present greater general isolation are those who belong to seriously dysfunctional families. Research conducted by other authors collaborate these results [72], whilst others such as Twenge, Spitzburg, and Campbell [73] did not manage to demonstrate that isolation in adolescents is more linked to one type of family over another type. These authors instead found high levels of isolation within adolescents coming from functional families.…”
Section: Discussionmentioning
confidence: 95%
“…More recently, nationally representative surveys of US adolescents 1976-2017, showed that compared to previous generations, adolescents in the 2010s spent less time on in-person (face-to-face) social interaction with peers. In 2016, college-bound high school seniors (vs. the late 1980s) spent an hour less a day engaging in in-person social interaction (Twenge et al 2019). Surveys indicated that adolescents' feelings of loneliness increased sharply after 2011.…”
Section: Introductionmentioning
confidence: 99%
“…They found that iGen adolescents (i.e., born after 1995) invested significantly less time on print media, television, and movies in the 2010s than adolescents in previous decades. Using the same methodology but different surveys of over 8 million respondents over four decades, Twenge et al () found that, from 1976 to 2017, iGen adolescents in particular spent decreasing time on face‐to‐face interactions, increasing time on digital media, and experienced sharp increases in loneliness after 2011 that was most pronounced among those low in in‐person interaction and high in social media use. These patterns occurred at the cohort level, even though, at the individual level, time spent on social media corresponded with more time spent with friends.…”
Section: Parameters Of Relational Spacementioning
confidence: 99%
“…In general, as relating increases between two or more people over time, relationships evolve and, in general, become more personal (Burke & Kraut, 2014). Such relating is increasingly mediated (Twenge, Campbell, & Spitzberg, 2019). Thus, the social becomes the relational, as well as the personal, even if interactants often do not perceive the mediated mode of such interactions as negotiations of their personal relationships (Hall, 2018).…”
Section: Introductionmentioning
confidence: 99%